A inclusão educacional e o envelhecimento:análise crítica a partir do Programa BRasil Alfabetizado - Barros, Simone da Cunha Tourino (2019)
The aim of this thesis was to understand the insertion of the aged worker into the educational policy of coping with illiteracy through the actions and results of the Brazilian Literate Program (PBA) in the period from 2003 to 2016 implemented by SECAD / SECADI. we start from the assumption that, still lack access to education, and this is an important mediation for political emancipation. Aged workers without access to education can not even attain political emancipation, which leads to little popular pressure for guaranteeing rights and their enforcement in the capitalist order. In addition, we defend the thesis of the myth of the educational inclusion of the aged workers, considering that the inclusion propagated by the Ministry of Education and specifically by SECADI through the Brazil Literacy Program, has not served this audience in their educational needs. In order to reach the proposed objectives, we carried out bibliographical and documentary research, reaching the result that despite the discourse of PBA's educational inclusion, propitiating the current logic of spreading a State committed to all citizens, we learn that the actions did not reach the objectives established in terms of access, permanence and continuity in the studies, as well as in the quality of the desired education. The conditions of the teaching and learning process reinforce the logic of a residual policy for the working class carried out by volunteers in spaces adapted for teaching and with bags with small values. The high rates of dropout and non-literacy of aging workers in the PBA express the myth of educational inclusion.